Trans-arterial positive ICG staining-guided laparoscopic liver watershed resection for hepatocellular carcinoma - Qian, Xinye; Hu, Wang; Gao, Lu; Xu, Jingyi; Wang, Bo; Song, Jiyong; Yang, Shizhong; Lu, Qian; Zhang, Lin; Yan, Jun; Dong, Jiahong (Frontiers in Oncology, 2022)
Introduction Anatomical liver resection is the optimal treatment for patients with resectable hepatocellular carcinoma (HCC). Laparoscopic Couinaud liver segment resection could be performed easily as liver segments could be stained by ultrasound-guided indocyanine green (ICG) injection into the corresponding segment portal vein. Several smaller liver anatomical units (liver watersheds) have been identified (such as S8v, S8d, S4a, and S4b). However, since portal veins of liver watersheds are too thin to be identified under ultrasound, the boundaries of these liver watersheds could not be stained intraoperatively, making laparoscopic resection of these liver watersheds demanding. Digital subtraction angiography (DSA) could identify arteries of liver watersheds with a diameter of less than 2 mm. Yet, its usage for liver watershed staining has not been explored so far. Purpose The aim of this study is to explore the possibility of positive liver watershed staining via trans-arterial ICG injection under DSA examination for navigating laparoscopic watershed-oriented hepatic resection. Methods We describe, in a step-by-step approach, the application of trans-arterial ICG injection to stain aimed liver watershed during laparoscopic anatomical hepatectomy. The efficiency and safety of the technique are illustrated and discussed in comparison with the laparoscopic anatomical liver resection via ultrasound-guided liver segment staining. Results Eight of 10 HCC patients received successful trans-arterial liver watershed staining. The success rate of the trans-artery staining approach was 80%, higher than that of the ultrasound-guided portal vein staining approach (60%). Longer surgical duration was found in patients who underwent the trans-artery staining approach (305.3 ± 23.2 min vs. 268.4 ± 34.7 min in patients who underwent the ultrasound-guided portal vein staining approach, p = 0.004). No significant difference was found in major morbidity, reoperation rate, hospital stay duration, and 30-day and 90-day mortality between the 2 groups. Conclusions Trans-arterial ICG staining is safe and feasible for staining the aimed liver watershed, navigating watershed-oriented hepatic resection under fluorescence laparoscopy for surgeons.